2020
DOI: 10.1038/s41596-019-0265-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding chemical reactivity using the activation strain model

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
180
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 232 publications
(183 citation statements)
references
References 68 publications
3
180
0
Order By: Relevance
“…The Pauli repulsion, DE Pauli (z), accounts for the destabiliz-ing interaction between occupied orbitals (more precisely,b etween same-spine lectrons) and is responsible for steric repulsion. [34] The orbitali nteraction energy, DE oi (z), accountsf or donor-acceptor interactions of occupied orbitals on one fragment with unoccupied orbitals on the other (such as the HOMO-LUMO interaction) and polarization,t hat is, the mixing of empty and occupied orbitals on one fragment due to the presence of the other.Adetailed step-by-step protocol on how to perform and interpret the activation strain and energy decomposition analysiscan be found in reference [35].…”
Section: Molecular Orbital and Energy Decomposition Analysismentioning
confidence: 99%
“…The Pauli repulsion, DE Pauli (z), accounts for the destabiliz-ing interaction between occupied orbitals (more precisely,b etween same-spine lectrons) and is responsible for steric repulsion. [34] The orbitali nteraction energy, DE oi (z), accountsf or donor-acceptor interactions of occupied orbitals on one fragment with unoccupied orbitals on the other (such as the HOMO-LUMO interaction) and polarization,t hat is, the mixing of empty and occupied orbitals on one fragment due to the presence of the other.Adetailed step-by-step protocol on how to perform and interpret the activation strain and energy decomposition analysiscan be found in reference [35].…”
Section: Molecular Orbital and Energy Decomposition Analysismentioning
confidence: 99%
“…1-Benzyl-3-cyclohexyl-5-iodo-4-phenyl-1H-pyrazolo [3,4-b]pyridine 17 was obtained as a white solid (1.03 g, 84 %). Upon scaling-up of this reaction on 3.77 g of 16, 1-benzyl-3-cyclohexyl-5-iodo-4-phenyl-1H-pyrazolo [3,4- 2929, 2851, 1551, 1483, 1442, 1347, 1271, 1189, 1175 (Z)-2-(2-(1-Cyclohexyl-3-phenylprop-2-yn-1-ylidene)hydrazinyl)-5-iodopyrimidine (18). To a Schlenk tube containing dry 3Å molecular sieves (100 mg) were successively added 2-hydrazinyl-5-iodo-pyrimidine 10 (112.5 mg, 0.48 mmol), THF (2.4 mL, 0.2 M), 1-cyclohexyl-3-phenylprop-2-yn-1-one 15 (131.55 mg, 0.62 mmol) and trifluoroacetic acid (5 μL, 0.067 mmol, 15 mol%) under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] A limitation of this conceptually interesting synthesis of pyridines are the high temperature (up to 280 °C under classical conditions 6 ) and very long reaction times that are required [7][8][9] to overcome the intrinsic lack of reactivity of these aza-dienes. [10][11][12][13][14][15][16][17][18][19] On the other hand, we recently reported that pyrimidines substituted in the 2-position by an (alkynyl)hydrazone could be exceptionally activated towards intramolecular [4ps+2ps] cycloadditions by a simple activation (Scheme 1, A). 20 In a practical one-pot procedure starting from 2-hydrazinopyrimidine 2, it was shown that condensation with ynone 3 in the presence of catalytic amount of trifluoroacetic acid was rapid at 60 °C in THF, leading to hydrazone 4.…”
Section: Introductionmentioning
confidence: 99%
“…To further understand the steric and electronic factors inuencing the head-to-head vs. head-to-tail regioselectivity, we applied the distortion-interaction 91,92 /activation strain (DI-AS) model [92][93][94][95][96] to the TSs for the formation of rst C-C bond for the present reaction (Fig. 3).…”
Section: Computational Electrochemical Potentialsmentioning
confidence: 99%
“…We further applied the method of energy decomposition analysis (with the ALMO-EDA method), [97][98][99] as applied in other similar systems, 94,96,[100][101][102] to break down the contributions to the interaction energy between the reacting fragments into the repulsive exchange energy due to Pauli's principle, E Pauli , the (semi-)classical electrostatic interaction energy between the charge densities of the fragments, E elec , the orbital interaction energies between the fragments as the TS occurs, E orb , and the dispersion energy between the fragments E disp . Comparing the EDA between the major, anti-adduct via ts1 to other TSs (Fig.…”
Section: Computational Electrochemical Potentialsmentioning
confidence: 99%